Quantification of bands produced by isoelectric focusing using immunoperoxidase. Issue 10 (October 1984) - Paluch, U H; Keir, G; Moyle, S; Thompson, E J
Abstract : An improved, rapid, and sensitive (to autoradiographic levels) method for the quantification of IgG bands from cerebrospinal fluid is presented. The principle of an internal standard is employed using the discrete bands of a paraprotein to correct for any run to run variability in the enzyme detection system which is linked to the immunoassay of immobilised antigen.